Question
upstudy study bank question image url

answers: 1.. \( x+y=10 \) \[ x-y=2 \] 2. \( x+y=5 \) 3. \( 2 x+3 y=11 \) \( 4 y-2 x=10 \) 4. \[ 3 x+2 y=13 \] \[ 2 x+3 y=18 \] \[ 8 x=7-3 y \] 6. 5. \( 8 x=7-3 y \) \( 3 x+4 y=3 \) \[ 9 y=-20 x+13 \] \( 6 x=7-10 y \) 7. \( 2 y=3 x+3 \) 8. \( 3 y-4 x=4 \) \( 2 y=x \) \( 8 x-1=-2 y \) 9. \( 4 y=-x \) 10. \[ \begin{array}{l} 3 y+6=6 x \\ x=2 y-2 \end{array} \]

Ask by King Medina. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the solutions to the systems of equations: 1. \( x = 6 \), \( y = 4 \) 2. Infinite solutions: \( y = 5 - x \) 3. \( x = 1 \), \( y = 3 \) 4. No solution 5. No solution 6. Infinite solutions: \( y = \frac{3}{2}x + \frac{3}{2} \) 7. No solution 8. Infinite solutions: \( y = -\frac{1}{4}x \) 9. \( x = 2 \), \( y = 2 \)

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3y+6=6x\\x=2y-2\end{array}\right.\) - step1: Substitute the value of \(x:\) \(3y+6=6\left(2y-2\right)\) - step2: Expand the expression: \(3y+6=12y-12\) - step3: Move the expression to the left side: \(3y-12y=-12-6\) - step4: Add and subtract: \(-9y=-12-6\) - step5: Add and subtract: \(-9y=-18\) - step6: Change the signs: \(9y=18\) - step7: Divide both sides: \(\frac{9y}{9}=\frac{18}{9}\) - step8: Divide the numbers: \(y=2\) - step9: Substitute the value of \(y:\) \(x=2\times 2-2\) - step10: Calculate: \(x=2\) - step11: Calculate: \(\left\{ \begin{array}{l}x=2\\y=2\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=2\\y=2\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(2,2\right)\) Solve the system of equations \( x+y=10;x-y=2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x+y=10\\x-y=2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=10-y\\x-y=2\end{array}\right.\) - step2: Substitute the value of \(x:\) \(10-y-y=2\) - step3: Subtract the terms: \(10-2y=2\) - step4: Move the constant to the right side: \(-2y=2-10\) - step5: Subtract the numbers: \(-2y=-8\) - step6: Change the signs: \(2y=8\) - step7: Divide both sides: \(\frac{2y}{2}=\frac{8}{2}\) - step8: Divide the numbers: \(y=4\) - step9: Substitute the value of \(y:\) \(x=10-4\) - step10: Calculate: \(x=6\) - step11: Calculate: \(\left\{ \begin{array}{l}x=6\\y=4\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=6\\y=4\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(6,4\right)\) Solve the system of equations \( 2 x+3 y=11;4 y-2 x=10 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x+3y=11\\4y-2x=10\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{11-3y}{2}\\4y-2x=10\end{array}\right.\) - step2: Substitute the value of \(x:\) \(4y-2\times \frac{11-3y}{2}=10\) - step3: Simplify: \(7y-11=10\) - step4: Move the constant to the right side: \(7y=10+11\) - step5: Add the numbers: \(7y=21\) - step6: Divide both sides: \(\frac{7y}{7}=\frac{21}{7}\) - step7: Divide the numbers: \(y=3\) - step8: Substitute the value of \(y:\) \(x=\frac{11-3\times 3}{2}\) - step9: Calculate: \(x=1\) - step10: Calculate: \(\left\{ \begin{array}{l}x=1\\y=3\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=1\\y=3\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(1,3\right)\) Solve the system of equations \( 3 x+2 y=13;2 x+3 y=18;8 x=7-3 y \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3x+2y=13\\2x+3y=18\\8x=7-3y\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{13-2y}{3}\\2x+3y=18\\8x=7-3y\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left\{ \begin{array}{l}2\times \frac{13-2y}{3}+3y=18\\8\times \frac{13-2y}{3}=7-3y\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}\frac{2\left(13-2y\right)}{3}+3y=18\\\frac{8\left(13-2y\right)}{3}=7-3y\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}y=\frac{28}{5}\\\frac{8\left(13-2y\right)}{3}=7-3y\end{array}\right.\) - step5: Substitute the value of \(y:\) \(\frac{8\left(13-2\times \frac{28}{5}\right)}{3}=7-3\times \frac{28}{5}\) - step6: Simplify: \(\frac{24}{5}=-\frac{49}{5}\) - step7: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step8: Rewrite: \((x, y) \in \varnothing\) Solve the system of equations \( 3 y-4 x=4;2 y=x;8 x-1=-2 y \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3y-4x=4\\2y=x\\8x-1=-2y\end{array}\right.\) - step1: Rewrite the expression: \(\left\{ \begin{array}{l}3y-4x=4\\x=2y\\8x-1=-2y\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left\{ \begin{array}{l}3y-4\times 2y=4\\8\times 2y-1=-2y\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}-5y=4\\16y-1=-2y\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}y=-\frac{4}{5}\\16y-1=-2y\end{array}\right.\) - step5: Substitute the value of \(y:\) \(16\left(-\frac{4}{5}\right)-1=-2\left(-\frac{4}{5}\right)\) - step6: Simplify: \(-\frac{69}{5}=\frac{8}{5}\) - step7: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step8: Rewrite: \((x, y) \in \varnothing\) Solve the system of equations \( 8 x=7-3 y;3 x+4 y=3;9 y=-20 x+13;6 x=7-10 y \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}8x=7-3y\\3x+4y=3\\9y=-20x+13\\6x=7-10y\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{7-3y}{8}\\3x+4y=3\\9y=-20x+13\\6x=7-10y\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left\{ \begin{array}{l}3\times \frac{7-3y}{8}+4y=3\\9y=-20\times \frac{7-3y}{8}+13\\6\times \frac{7-3y}{8}=7-10y\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}\frac{3\left(7-3y\right)}{8}+4y=3\\9y=-\frac{5\left(7-3y\right)}{2}+13\\\frac{3\left(7-3y\right)}{4}=7-10y\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}y=\frac{3}{23}\\9y=-\frac{5\left(7-3y\right)}{2}+13\\\frac{3\left(7-3y\right)}{4}=7-10y\end{array}\right.\) - step5: Substitute the value of \(y:\) \(\left\{ \begin{array}{l}9\times \frac{3}{23}=-\frac{5\left(7-3\times \frac{3}{23}\right)}{2}+13\\\frac{3\left(7-3\times \frac{3}{23}\right)}{4}=7-10\times \frac{3}{23}\end{array}\right.\) - step6: Simplify: \(\left\{ \begin{array}{l}\frac{27}{23}=-\frac{81}{23}\\\frac{114}{23}=\frac{131}{23}\end{array}\right.\) - step7: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step8: Rewrite: \((x, y) \in \varnothing\) Let's solve the systems of equations step by step based on the provided inputs. ### 1. System: \[ x + y = 10 \] \[ x - y = 2 \] **Solution:** By solving these equations, we find: \[ (x, y) = (6, 4) \] ### 2. System: \[ x + y = 5 \] **Solution:** This is a single equation with infinite solutions. We can express \(y\) in terms of \(x\): \[ y = 5 - x \] ### 3. System: \[ 2x + 3y = 11 \] \[ 4y - 2x = 10 \] **Solution:** By solving these equations, we find: \[ (x, y) = (1, 3) \] ### 4. System: \[ 3x + 2y = 13 \] \[ 2x + 3y = 18 \] \[ 8x = 7 - 3y \] **Solution:** This system has no solution, which can be expressed as: \[ (x, y) \in \varnothing \quad \text{(No solution)} \] ### 5. System: \[ 8x = 7 - 3y \] \[ 3x + 4y = 3 \] \[ 9y = -20x + 13 \] \[ 6x = 7 - 10y \] **Solution:** This system also has no solution: \[ (x, y) \in \varnothing \quad \text{(No solution)} \] ### 6. System: \[ 2y = 3x + 3 \] **Solution:** This is a single equation with infinite solutions. We can express \(y\) in terms of \(x\): \[ y = \frac{3}{2}x + \frac{3}{2} \] ### 7. System: \[ 3y - 4x = 4 \] \[ 2y = x \] \[ 8x - 1 = -2y \] **Solution:** This system has no solution: \[ (x, y) \in \varnothing \quad \text{(No solution)} \] ### 8. System: \[ 4y = -x \] **Solution:** This is a single equation with infinite solutions. We can express \(y\) in terms of \(x\): \[ y = -\frac{1}{4}x \] ### 9. System: \[ 3y + 6 = 6x \] \[ x = 2y - 2 \] **Solution:** By solving these equations, we find: \[ (x, y) = (2, 2) \] ### Summary of Solutions: 1. \( (x, y) = (6, 4) \) 2. Infinite solutions: \( y = 5 - x \) 3. \( (x, y) = (1, 3) \) 4. No solution 5. No solution 6. Infinite solutions: \( y = \frac{3}{2}x + \frac{3}{2} \) 7. No solution 8. Infinite solutions: \( y = -\frac{1}{4}x \) 9. \( (x, y) = (2, 2) \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Ever wondered why solving systems of equations is like playing a puzzle game? Each equation is a piece of the puzzle, and when you find the solution, you reveal the whole picture! Historically, systems of equations have their roots in the works of mathematicians like Euclid and Diophantus, who laid the groundwork for algebraic methods that later evolved into what we use in modern math. When applying these concepts in real life, think of a cash register balancing calculations or planning ingredients for a recipe. For example, if you know your total budget and the price of each item, you can set up equations to figure out quantities—just like blending flavors in a dish to achieve the perfect taste.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy